The Impact of Organizational Commitment in Promoting Emotional Work (Applied study in a sample of private hospitals in Baghdad governorate) - Hasan, Amal Mansoor (Journal of Economic, Administrative and Legal Sciences, 2020)
This research aims to identify the impact of organizational commitment in promoting emotional work by promoting competition among private hospitals (Study Sample). The research was based on the hypothesis that represented by the existence of an impact relationship between the research variables by analyzing the answers of the research sample, which included a number of private hospitals in Baghdad by distributing the questionnaire form to the employees working in the hospitals (study sample) which was (120) questionnaires, and after collected was (93) questionnaires only a valid form for statistical analysis using the Smart PLS program and descriptive analysis so a number of conclusions were reached, most notably are the following: - A clear impact relationship of organizational commitment in promoting emotional work. - There is a good correlation between the independent variable (organizational commitment) and the dependent variable (emotional work). The researcher presented a set of recommendations based on his findings, the most important of which is to consolidate the organizational commitment in the organization, especially the emotional commitment because it is based on the degree of individual engagement in hospitals (study sample).